PENGARUH PENGALAMAN MENGAJAR, ETOS KERJA DAN MOTIVASI MENGAJAR TERHADAP KINERJA GURU SMK NEGERI 1 SIBOLGA - Dahlia Elisah Ritonga; Rosmida Pohan; Romauli Sianturi; Ganda Roy Hutagalung; Gibson H. Purba (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
The purpose of this research was to determine and analyze the influence of teaching experience, work ethics and teaching motivation on the performance of teachers of SMK Negeri 1 Sibolga, both partially and simultaneously. The sample in this research were all employees, amounting to 55 teachers. Determination of the number of samples using a saturated sample (census). The analysis technique used is descriptive analysis method and multiple linear regression analysis with SPSS 20.00 for windows. The results showed that : 1) Teaching Experience had a positive and significant effect on the performance of teachers of SMK Negeri 1 Sibolga, where the value of tcount (2.161) ttable (1.675) and the probability level of 0.035 0.05; 2) Work Ethics has a positive and significant effect on the performance of teachers of SMK Negeri 1 Sibolga, where the value of tcount (2.225) ttable (1.675) and probability value of 0.031 0.05; 3) Teaching Motivation has a positive and significant effect on the performance of teachers of SMK Negeri 1 Sibolga, where the value tcount (6.341) ttable (1.675) and probability value of 0.000 0.05; 4) Teaching experience, work ethic and teaching motivation are positive and significant to the performance of teachers of SMK Negeri 1 Sibolga, where the value of Fcount (24,977) Ftable (2,786) and probability 0,000 0.05. Teaching experience, work ethic and teaching motivation explain its influence on teacher performance by 57.1%, while the remaining 42.9% is requested by other variables not examined in this research.